Dhamma chakra ke uss paar - Nautiyal, Mukesh (Dehradun Samay sakshay, 2017)
Dhamma Chakra Ke Us Paar' is a spectacular collection of the fifteen stories written by an eminent Himalayan writer Mr. Mukesh Nautiyal. He has crafted these stories through his vast 3 decades experience of writing. While reading these stories of unresolved mysteries of Himalaya, reader connects and walks with author and witness the divine sound of breathtaking waterfalls, angels doing music like Vegas$1 (BMagicians, listen the lull of abandoned villages and the Mugal music mystery of Himalaya$1 (Bs high altitude meadows. Almost all stories are based on folk-lore, traditionally exists in the mysteries abode of the Ganga.s
Keywords: Fiction